Performance Assessment of GaAs Pocket-Doped Dual-Material Gate-Oxide-Stack DG-TFET at Device and Circuit Level - Km. Sucheta Singh; Satyendra Kumar; Saurabh Chaturvedi; Kapil Dev Tyagi; Vaibhav Bhushan Tyagi (IET Circuits, Devices and Systems)
This study explores the impact of integrating a gallium arsenide (GaAs) pocket at the source and drain in a dual-material gate-oxide-stack double-gate tunnel field-effect transistor (DMGOSDG-TFET). The performance of this DMGOSDG-TFET, employing work-function engineering and gate-oxide-stack techniques, is compared with a GaAs pocket-doped DMGOSDG-TFET. Using the Silvaco Technology Computer-Aided Design tool, the comparison covers DC characteristics, analog/RF behavior, and circuit-level assessments. The research introduces an optimized heterostructure pocket-doped DMGOSDG-TFET to enhance DC characteristics, analog/RF performance, and DC/transient analysis. This novel architecture effectively suppresses ambipolarity, making it more suitable for current conduction. The incorporation of work-function engineering and a gate-oxide-stack approach enhances the device’s current driving capability, while the use of a highly doped GaAs pocket at the source and drain virtually eliminates ambipolar current conduction. Simulation results indicate that the proposed heterostructure device exhibits a high ON-current and switching ratio. For analog/RF applications, the optimized heterostructure device outperforms conventional DMGOSDG-TFET, offering higher cutoff frequency, transconductance, and other analog/RF parameters. Circuit-level performance is assessed using HSPICE, with a focus on the implementation of a resistive-load inverter for both proposed and conventional device topologies through DC and transient evaluations.